Treating Thyroid Associated Ophthalmopathy in Pediatric Patients - Dong, Tianyu; Fu, Zhujun; Wang, Xu (Frontiers in Endocrinology, 2022)
Thyroid associated ophthalmopathy (TAO) is a common extra-thyroid clinical manifestation of Graves' disease. It is an inflammatory disease of the eye and orbital tissues. Up to one-third of pediatric Graves' disease patients could be diagnosed with TAO. The symptoms can be variable with remissions and exacerbations of pediatric Graves’ disease, which has negative effects on the quality of life in children. Teprotumumab is a fully human IgG1κ type monoclonal antibody targeting insulin-like growth factor-1 receptor (IGF-1R), and was approved for the treatment of TAO as a “breakthrough therapy” by the FDA in 2020. Nevertheless, the safety and effectiveness have not been established in pediatric patients. More efforts would be made for the further development of teprotumumab for pediatric use. IGF-1R plays an important role in human development, which raises concerns of developmental toxicity. As presented in the pharmacology review report, juvenile monkeys were tested in two separate repeated-dose toxicity studies and no NOAEL was identified. Teprotumumab affected the growth, thymus, spleen and decreased the bone growth. Younger animals seemed to be more sensitive to the effects on normal growth and normal thymus. Hearing impairment posed additional risk to the potential pediatric use, especially for school-age children. Considering the nature of the target, Teprotumumab should not be used empirically in children. More efforts would be made for the further development of teprotumumab for pediatric use.